Radiologically Undetected Hepatocellular Carcinoma in Patients Undergoing Liver Transplantation: An Immunohistochemical Correlation With LI-RADS Score. (November 2017) - Xiong, Wei; Cheeney, Gregory; Kim, Sooah; Kolesnikova, Violetta; Henninger, Brooke; Alexander, Jacob; Swanson, Paul E.; Upton, Melissa P.; Truong, Camtu D.; Yeh, Matthew M.
Abstract : Orthotopic liver transplantation is the best option for patients with carefully selected unresectable disease because of underlying liver dysfunction. The 5-year survival rate after orthotopic liver transplantation for early detected hepatocellular carcinoma (HCC) is high, and a similar or even higher rate is reported in those with radiologically undetected HCC. This study evaluated and compared the histologic features of pretransplant radiologically undetected (14 patients, 25 tumors) versus detected (36 patients, 45 tumors) HCCs. Tumor size, tumor differentiation, number of unpaired arteries, mitotic count per 10 high-power fields, CD34 immunostain to assess microvessel density, and Ki67 immunostain were compared with the Liver Imaging Reporting and Data System score, which was retrospectively assigned to each tumor in both groups. The Liver Imaging Reporting and Data System score was significantly higher in the HCC detected group ( P <0.001). The vast majority of the undetected HCCs (88%) was <2 cm in size. Only 12% of the undetected HCCs were ≥2 cm, whereas 51% of the detected HCCs were ≥2 cm in size. Higher rate of moderate to poor tumor differentiation was noted in the detected HCCs compared with the undetected group (89% vs. 60%; P =0.004). No statistically significant difference in the number and distribution of unpaired arteries, or mitotic count was observed in 2 groups (although fewer unpaired arteries were identified in the undetected group). The detected HCCs had a higher rate of 2+ CD34 staining compared with the undetected HCCs (68% vs. 27%; P =0.002), whereas the opposite was observed for 1+ CD34 staining (59% undetected HCCs vs. 17% detected HCCs; P =0.002). Ki67 proliferative index was not statistically different between the 2 groups (120.8/1000 cells detected HCCs vs. 81.8/1000 cells undetected HCCs; P =0.36). The factors associated with failing to detect HCCs pretransplant by radiologic studies include small tumor size (<2 cm), low-grade histologic differentiation, and low microvessel density (low CD34 staining). A significant association between the number and distribution of unpaired arteries and HCC detection has not been established by our study.